The Establishing Paradigm of Dominus Litis Principle in Indonesian Administrative Justice - Soehartono Soehartono; Kukuh Tejomurti; Arsyad Aldyan; Rachma Indriyani (Sriwijaya Law Review, 2021)
This study aimed to analyse a shifting paradigm of Dominus Litis (judge activeness) in the Indonesian state administrative justice. This principle emphasises that judges expand the paradigm that judges are not limited to being used in processes regulated in law. However, judges need to actively develop the paradigm to make legal discoveries oriented towards substantive justice and expand the paradigm from merely resolving disputes positivistically to resolving conflicts with paradigms. Legal realism and sociological jurisprudence to create substantive justice. This paper uses the normative research method, with a statutory approach and case approach by analysing two decisions of state administrative court judges. The result showed that Dominus Litis in the dispute's accomplishment is not limited to the implementation of juridical-legal positivism factors, but on how judges use their mindset to provide ideal decisions and conduct legal reasoning use socio-legal and socio-cultural paradigms. The development of demands for justice has also experienced a paradigm shift of justice. It requires the principle of an active judge who always follows developments in public policy, such as the principle of sustainable development related to environmental and natural resource issues, and finding the legal material truth.